Subacute Schlerosing Panencephalitis - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1987)
A 10-year old Nicaraguan boy with SSPE was treated with intraventricular biosynthetic alpha 2b interferon (Schering, Intron A) 1 million units twice weekly for 5h months, at the Children's Hospital of Los Angeles, Neurology Division, Los Angeles, CA.